The Influence of Sports Participation on Body Image, Self-Efficacy, and Self-Esteem in College Students - Ouyang, Yiyi; Wang, Kun; Zhang, Tingran; Peng, Li; Song, Gan; Luo, Jiong (Frontiers in Psychology, 2020)
Objectives This study aimed to explore the relationship between body image, self-efficacy, self-esteem, and sports participation by gender, grade, and specialty and then to provide a reference for promoting participation in sports and physical activities in college students. Methods Using stratified random sampling, undergraduate students in western China were selected as participants. The data obtained in this study were processed by SPSS 19.0 and AMOS 21.0 statistical software. Results Body image was significantly positively correlated with self-efficacy, self-esteem, and sports participation. Self-efficacy was significantly positively correlated with self-esteem and sports participation. Self-esteem was significantly positively correlated with sports participation. Body image had a direct effect on sports participation, with an effect value of 0.124. Furthermore, the mediating effects of self-efficacy (0.079) and self-esteem (0.108) were significant in the relationship between body image and sports participation. Meanwhile, the chain mediating role of self-efficacy–self-esteem was also obvious (0.035). Conclusion Body image, self-efficacy, and self-esteem had significant influence on sports participation in college students. At the same time, the mediating effect of self-efficacy, self-esteem, and self-efficacy–self-esteem on body image and sports participation were established, and self-esteem was the key factor to sports participation.